IMPROVING SENIOR HIGH SCHOOL STUDENTS’ ABILITY IN COMPREHENDING DESCRIPTIVE TEXT BY USING RECIPROCAL TEACHING TECHNIQUE - FAIRISTYA EMBRYANY; Aryuliva Adnan (Journal of English Language Teaching, 2017)
The writer will discuss about teaching reading comprehension to senior high school by using the reciprocal teaching technique. This technique was firstly introduced by Annemarie Palinscar and Ann Brown in 1984.There are several goals in implementing the reciprocal teaching technique on descriptive text, such as to help students finding main ideas and specific information in the text and to help students in improving the vocabulary. This technique is not only limited to descriptive text, but also to many other kinds of text. By using this technique, the students are expected to be more interested in reading since they are actively involved in the process.Teaching reading comprehension by using the reciprocal teaching technique consists of four stages such as predicting, questioning, clarifying, dan summarizing. The activity begins with what the students have already known about descriptive text. After that, the teacher introduces each stage of the reciprocal teaching technique by modelling them. When the students have understood each stage, they are then divided into a group of four or more. Then, they begin to perform each stage of the reciprocal teaching technique.